Hemophagocytic Lymphohistiocytosis Due to Disseminated Histoplasmosis in a Young Patient with AIDS - Zachary Mostel; James Speed Rogers; Sushrita Neogi (Journal of Global Infectious Diseases)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening syndrome of immune dysregulation that results in multiorgan failure; HIV and histoplasmosis are known triggers of HLH. A young patient with AIDS was found to have disseminated histoplasmosis and met criteria for HLH. Despite 10 days of treatment with liposomal amphotericin B, she developed shock and acute respiratory distress syndrome and ultimately died. The few reported cases of HLH due to histoplasmosis in AIDS offer a variety of treatment approaches. There have been successful outcomes combining amphotericin with chemotherapies for HLH. Targeted therapies for HLH may be considered on a case-by-case basis in the setting of concurrent disseminated histoplasmosis and HIV/AIDS.